COMPARATIVE ASPECTS OF THE MAIN SKI SCHOOLS IN THE WORLD - Tudor BOGDAN; Lăcrimioara LAZĂR (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2015)
Alpine skiing is one of the most practiced winter sports due to accessibility and attractiveness of which enjoys these sports nowadays. This situation has helped the development of tourism services, aligned ski areas, ski equipment and materials industry, and current guidelines and methodical sequence learning pedagogy of skiing, all putting in the spotlight client, the individual and his personal issues. We speak of an orientation towards the individual needs of each of us, in order to give us a greater psychological comfort, a general feeling of well (well-being). In this idea, both methodology and pedagogy of teaching and learning of skiing (because of this discipline sports talk here) was centered on the learner, existing, internationally, a tendency to uniformity of content learning skiing to the detriment of divergent opinions that were promoted by some ski schools in the world. For a better understanding of the phenomenon of learning ski, we present in a comparative manner, the conception of the main ski schools in the world. The main points of comparison are the teaching progression in ski, and the motor skills.